2020
DOI: 10.3390/pathogens9121024
|View full text |Cite
|
Sign up to set email alerts
|

Bactericides Based on Copper Nanoparticles Restrain Growth of Important Plant Pathogens

Abstract: Copper nanoparticles (CuNPs) can offer an alternative to conventional copper bactericides and possibly slow down the development of bacterial resistance. This will consequently lower the accumulation rate of copper to soil and water and lower the environmental and health burden imposed by copper application. Physical and chemical methods have been reported to synthesize CuNPs but their use as bactericides in plants has been understudied. In this study, two different CuNPs products have been developed, CuNP1 an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
25
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 47 publications
3
25
0
1
Order By: Relevance
“…The ATR method was utilized to detect the characteristic peaks of CuNPs. ATR spectra of CuNPs Types 1 and 2 presented similar stretching and bending frequencies to a previous study within our group [5], showing, in brief, the presence of four characteristic bands of stabilizer S1 as well as the symmetrical stretching and bending vibration of Cu-O bond (CuNP Type 1). In the same context, ATR spectrum of CuNP Type 2 indicated that copper oxide and copper hydroxide are the prevalent copper species and presented the six characteristic peaks of stabilizer S2.…”
Section: Atr Measurementssupporting
confidence: 81%
See 3 more Smart Citations
“…The ATR method was utilized to detect the characteristic peaks of CuNPs. ATR spectra of CuNPs Types 1 and 2 presented similar stretching and bending frequencies to a previous study within our group [5], showing, in brief, the presence of four characteristic bands of stabilizer S1 as well as the symmetrical stretching and bending vibration of Cu-O bond (CuNP Type 1). In the same context, ATR spectrum of CuNP Type 2 indicated that copper oxide and copper hydroxide are the prevalent copper species and presented the six characteristic peaks of stabilizer S2.…”
Section: Atr Measurementssupporting
confidence: 81%
“…The synthesized CuNPs presented a mean diameter range between 4.90 and 10.41 nm. The narrow size distribution and small size ensure a higher antimicrobial activity [ 5 ]. The resulted CuNPs were characterized among the lowest diameters reported in the literature [ 12 , 41 , 42 , 43 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The Pseudomonas syringae pv. tomato susceptibility test against B. amyloliquefaciens MBI600 was performed in 96-well microplates (Greiner CELLSTAR 96-well microplates, F-bottom) as previously described ( 73 , 74 ). In brief, P. syringae pv.…”
Section: Methodsmentioning
confidence: 99%